2012
DOI: 10.2146/ajhp110725
|View full text |Cite|
|
Sign up to set email alerts
|

Newer oral anticoagulants: A review of laboratory monitoring options and reversal agents in the hemorrhagic patient

Abstract: Although there is currently no gold standard of measurement for any of the newer anticoagulants, the published literature enables practitioners to evaluate the efficacy and sensitivity of a majority of these assays. Prohemostatic agents can be used in instances of severe, life-threatening hemorrhagic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
137
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(137 citation statements)
references
References 61 publications
(71 reference statements)
0
137
0
Order By: Relevance
“…The Randomized Evaluation of Long-term Anticoagulant Therapy (RE-LY trial) reported a 1.45% per year incidence of lifethreatening bleeding or death related to bleeding complications from treatment with dabigatran, and this led to safety advisories being issued in several countries. 6,13 Agents that may be used to reverse the effects of dabigatran such as the activated prothrombin complex concentrate (FEIBA; Baxter, Deerfield, Illinois) and the recently approved 4-component prothrombin complex concentrate (Kcentra; CSL Behring, King of Prussia, Pennsylvania) may be effective, but without laboratory guidance the dosing is difficult, and thrombosis may result.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…The Randomized Evaluation of Long-term Anticoagulant Therapy (RE-LY trial) reported a 1.45% per year incidence of lifethreatening bleeding or death related to bleeding complications from treatment with dabigatran, and this led to safety advisories being issued in several countries. 6,13 Agents that may be used to reverse the effects of dabigatran such as the activated prothrombin complex concentrate (FEIBA; Baxter, Deerfield, Illinois) and the recently approved 4-component prothrombin complex concentrate (Kcentra; CSL Behring, King of Prussia, Pennsylvania) may be effective, but without laboratory guidance the dosing is difficult, and thrombosis may result.…”
Section: Commentmentioning
confidence: 99%
“…In some cases, there are no useful methods to detect and monitor these agents, and no ''antidotes'' are available to reverse their effects. Miyares and Davis 13 recently reviewed the usefulness and sensitivity of current coagulation assays for dabigatran, rivaroxaban, and apixaban. The most easily available tests for emergency situations, prothrombin time and partial thromboplastin time, were described as ''not ideal'' with the exception of the partial thromboplastin time for dabigatran.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Concentrated clotting factor products containing one or more clotting factors are available for use as alternatives to FFP for reversal of warfarin and other oral anticoagulants. There are four major types of products: [9][10][11][12][13][14][15][16] • rFVIIa (NovoSeven RT, Novo Nordisk…”
Section: S14mentioning
confidence: 99%
“…Especially in case of hemorrhagic complications or in patients with high bleeding risk, it may be necessary to quantify the anticoagulant effects of dabigatran (7,8). Dager et al (9) showed that for every 25 ng/mL of dabigatran, INR increased 0.03 to 0.07 depending up the reagent and aPTT increased 4.6 seconds in average.…”
Section: Discussionmentioning
confidence: 99%